Alsónyék-Bátaszék, Ungarn: Der größte neolithische Fundort in Mitteleuropa - Bánffy, Eszter (e-Forschungsberichte des DAI, 2023)
The Neolithic site Alsónyék-Bátaszék in the Carpathian Basin in Hungary was uncovered from 2006 to 2009 during rescue excavations. Within about 25 ha of ground 15.000 archaeological features were excavated of which 70% belong to settlements from almost all Neolithic periods (Starčevo, Linearbandkeramik [LBK], Sopot, Lengyel) and 2500 burials could be secured. Altogether they represent one of the largest known Neolithic sites in Europe as well as a valuable source for the research of contacts between the earliest farmers’ communities of the Southeast and the Northwest. The multidisciplinary analysis of this important site currently takes place under lead management of the Hungarian Academy of Sciences Budapest and the Romano-Germanic Commission.